1975
DOI: 10.1901/jeab.1975.23-3
|View full text |Cite
|
Sign up to set email alerts
|

REINFORCEMENT OF BEHAVIORAL PATTERNS: SHAPING A SCALLOP1

Abstract: Temporal patterns of key pecking by pigeons were shaped by a schedule in which the delivery of food was contingent upon a measure of the overall extent to which the temporal pattern of behavior within a 5-sec trial conformed to a required pattern. This pattern approximated a constant rate of change in the rate of key pecking throughout the 5-sec trial. In comparison with behavior maintained by a classical fixed-interval 5-sec schedule, the new schedule controlled a better approximation to a "scallop" within in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 12 publications
7
101
1
Order By: Relevance
“…Shimp (1975) has noted that under standard schedules of reinforcement, contingency and contiguity are confounded. In Shimp's terms, if one allows for an animal to remember recent behavior, then the reinforcer can strengthen behavior over a longer time span (Hawkes & Shimp, 1975;Shimp, 1975). Hawkes and Shimp (1975) demonstrated that under a short fixed interval (FI 5-s), a behavioral pattern of successively shorter IRTs could be shaped.…”
Section: Plo and P28 Showed Regular Variation In Thismentioning
confidence: 99%
See 1 more Smart Citation
“…Shimp (1975) has noted that under standard schedules of reinforcement, contingency and contiguity are confounded. In Shimp's terms, if one allows for an animal to remember recent behavior, then the reinforcer can strengthen behavior over a longer time span (Hawkes & Shimp, 1975;Shimp, 1975). Hawkes and Shimp (1975) demonstrated that under a short fixed interval (FI 5-s), a behavioral pattern of successively shorter IRTs could be shaped.…”
Section: Plo and P28 Showed Regular Variation In Thismentioning
confidence: 99%
“…In Shimp's terms, if one allows for an animal to remember recent behavior, then the reinforcer can strengthen behavior over a longer time span (Hawkes & Shimp, 1975;Shimp, 1975). Hawkes and Shimp (1975) demonstrated that under a short fixed interval (FI 5-s), a behavioral pattern of successively shorter IRTs could be shaped. Hawkes and Shimp (1975) chose to discuss their results in terms of short-term memory for recent behavior, but it is equally descriptive and perhaps more accurate to say that the reinforcer acts on more than the response that immediately preceded it (see Catania, 1971;Dews, 1969).…”
Section: Plo and P28 Showed Regular Variation In Thismentioning
confidence: 99%
“…Several researchers have provided data to show tha t fun ctional operants may include responses arranged into temporal and spatial groups , that is, that several of the responses that precede a reinforcer may be affected by the reinforcer (e.g., Grayson & Wasserman, 1979;Hawkes & Shimp , 1975 ;Pisacreta, 1982 ;Wasserman, 1977) . The present results are consistent with Shimp ' s (1976) position : ''The repeated delivery of a reinforc er afte r a behavioral pattern a few seconds in duration may strengthen the entire pattern and establish it as a functio nal unit.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 2 and 3 reveals that both birds made fewer errors on trials in which they showed a consistent stimulus preference. These parsimonious response patterns demonstrated that a reinforcer influences not only the response that produces it (the fifth response to white on Key 2), but also the four responses that were never directly followed by reinforcement (Catania, 1971;Hawkes & Shimp, 1975;Pisacreta, 1982;Schwartz , 1980 ;Wasserman, 1977). Specifically, strict response-reinforcer contiguity may not be essential for conditioning to occur (Shimp, 1976a(Shimp, , 1976bWasserman, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…Skinner's contingencies that shaped the spacing between successive key pecks or lever presses, like differential reinforcement of lowrate (DRL) schedules, were very early examples of the shaping method of Category 3. Later methods have shaped more complex multiple patterns, like multiple interresponse times (IRTs; Anger, 1956;Galbicka, 1994;Platt, 1973;Shimp, 1971Shimp, , 1973, IRTs and interchangeover times (ICTs) from several additional contingencies, and hierarchical patterns of increasing or decreasing rates of component responses that look like a fixed-interval scallop (Hawkes & Shimp, 1975, 1998. These varieties of shaped quantitative patterns presumably only scratch the surface of possible quantitative behaviors extended in time created through shaping.…”
Section: Category 3: a Unified Analysismentioning
confidence: 99%